2018
DOI: 10.2105/ajph.2018.304696
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Obesity Prevention Intervention in Low-Income Preschoolers: Primary and Subgroup Analyses of the NET-Works Randomized Clinical Trial, 2012–2017

Abstract: Objectives. To evaluate a multicomponent obesity prevention intervention among diverse, low-income preschoolers. Methods. Parent–child dyads (n = 534) were randomized to the Now Everybody Together for Amazing and Healthful Kids (NET-Works) intervention or usual care in Minneapolis, MN (2012–2017). The intervention consisted of home visits, parenting classes, and telephone check-ins. The primary outcomes were adjusted 24- and 36-month body mass index (BMI). Results. Compared with usual care, the NET-Works int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…The authors found no effect of the intervention on child BMI at age 2 or 3 years in the sample as a whole. However, they found reduced increases in BMI among Hispanic children and children with overweight or obesity at baseline and exposed to the intervention arm, with no differences by gender . Similar results were found from a mobile‐based intervention among preschoolers in Sweden, with larger effects of the intervention among those who were heavier at baseline …”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The authors found no effect of the intervention on child BMI at age 2 or 3 years in the sample as a whole. However, they found reduced increases in BMI among Hispanic children and children with overweight or obesity at baseline and exposed to the intervention arm, with no differences by gender . Similar results were found from a mobile‐based intervention among preschoolers in Sweden, with larger effects of the intervention among those who were heavier at baseline …”
Section: Discussionsupporting
confidence: 53%
“…French et al investigated the effect of a multicomponent obesity prevention intervention among preschool‐aged children of low‐income and racially/ethnically diverse parents in Minneapolis, MN. The intervention was a 3‐year randomized control trial including home visits to address parental behavior and home‐environment change in terms of children's eating and physical activity patterns, community‐based parenting classes, and primary care provider interactions (the control group received only the latter) . The authors found no effect of the intervention on child BMI at age 2 or 3 years in the sample as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] In particular, two recently conducted randomized trials among predominantly Latino families did not achieve their primary outcome of obesity prevention among preschool-aged children. 11,12 These findings are consistent with a previous systematic review that identified only a few successful interventions among Latino children, all of which were among older children. 13 One reason that childhood obesity interventions for children from low-income and minority communities may fail is that intervention content may not account for the wide variability of cultural, social, and psychological factors that contribute to both obesity and its determinative health behaviors.…”
supporting
confidence: 89%